Analisis Kebijakan Pendidikan: A Sytematic Literature Review - Agustini, Melati; Salsabila, Fatia; Khaira, Miswatul; Zulkhairi, Zulkhairi (Yayasan Putroe Ceudah Aceh, 2025)
Education is a strategic sector influenced by various dimensions, including social, economic, cultural, and political. Education policy plays a crucial role in determining the direction, quality, and equity of education services. This study aims to examine education policy analysis through a Systematic Literature Review (SLR) approach using the PRISMA method. Data were collected from articles in Google Scholar using the Publish or Perish 8 application, resulting in 100 articles, which were selected into nine relevant articles. The results indicate that education policy analysis has not been fully optimized in its implementation. Some of the main challenges identified include a lack of resources, weak implementation strategies, unclear policy visions, and mismatches between central policies and local conditions. Policy analysis encompasses the processes of problem identification, data collection, alternative formulation, and policy evaluation.